PERANCANGAN AWAL SUDU TURBIN ANGIN DENGAN KAPASITAS 3200 WATT - Vito Andika Permana; Ismoyo Haryanto (JURNAL TEKNIK MESIN, 2015)
The energy need for is increasing from year to year in line with the depletion of non-renewable energy resources. Therefore it is necessary to explore the potential of renewable energy resources in order to meet a demand. Wind turbines can be an alternative generator by converting wind energy into electricity amid the global energy crisis in the 21st century. At selected locations, namely the pond location on the coast of Kulon Progo, the electrical energy needs still rely on diesel generators. The objective of this thesis is to design a wind turbine that can meet the needs of the electrical energy from the pond to replace generators that use diesel fuel. This study aimed to get an airfoil that has maximum  and configuration as well as dimensions of horizontal axis wind turbine blade with a minimum capacity of 3200 W. Simulation an analysis we conducted by using Qblade software. The result showed that airfoil which has  most of the 34 airfoil being compared is Giguere SG6043 airfoil. Blade configuration that is designed to have a diameter of 10 m, the pitch angle of 1 degree, and 25 degree twist in position 0.31-0.62 m, 11 degrees in position 0.62-1.25m, 6 degrees in position 1.25-2.50 m, 2 degrees in position 2.50-3.75 m, and 0.41 degrees in position 3.75-5.00 m with maximum power of 3657 Watts at 56 rpm.